Fraud In The Digital Age: Assessing Cybercrime Through The Lens of The Fraud Hexagon - Prawitasari, Putu Putri (JAF (Journal of Accounting and Finance), 2025)
The rise of cybercrime in the digital era presents significant challenges for individuals, organizations, and governments. This paper explores the background and evolution of cybercrime and digital fraud, utilizing the Fraud Hexagon Theory to analyze the motivations behind fraudulent behavior. The COVID-19 pandemic has further accelerated cybercrime, emphasizing the urgent need for effective fraud detection and prevention strategies. The integration of big data analytics has emerged as a key approach in fraud detection, while corporate governance and internal controls play a crucial role in mitigating fraud risks. Through a systematic review of scholarly literature sourced from the Scopus database, this study examines various perspectives on fraud prevention in the digital landscape. It assesses the impact of digital transformation on cyber fraud, highlighting the role of advanced analytics and internal controls in combating fraudulent activities. Additionally, the study synthesizes research findings to provide insights into the evolving nature of fraud schemes and the necessity of adaptive fraud prevention strategies. By leveraging the Fraud Hexagon framework, this paper contributes to a deeper understanding of cyber fraud and offers recommendations for strengthening fraud detection and prevention efforts in the digital age.